Predictors of Depression and Suicidal Ideation of Filipino College Freshmen in a Philippine State College - Nick D. Alayon (Philippine Social Science Journal, 2021)
This study described the prevalence and predictors of depression and suicidal ideation of 365 Filipino college freshmen in a Philippine State College during the academic year 2019–2020. Utilizing a descriptive correlational design, psychosocial predictors were measured using the Bar-On EQ Inventory and participants' socio-demographic profile respectively. Depression and suicidal ideation were measured using Depression, Anxiety, and Stress Scale-21 and Columbia-Suicide Severity Rating Scale respectively. Emotional intelligence and family structure were inversely associated with depression and suicidal ideation while sex was associated with suicidal ideation. Parents/guardian's educational attainment was associated with depression and suicidal ideation. EQ and family structure were predictors of depression and suicidal ideation, while sex predicted suicidal ideation. Prevalent depression, higher suicidal tendencies among female students, and those living alone, and students' underdeveloped EQ point towards an urgency for gender-specific, psycho-socially oriented, and strategic school-based mental health program.